2008
DOI: 10.1111/j.1750-3841.2008.00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Coating of Peanuts with Edible Whey Protein Film Containing α‐Tocopherol and Ascorbyl Palmitate

Abstract: Physical properties of whey protein isolate (WPI) coating solution incorporating ascorbic palmitate (AP) and alpha-tocopherol (tocopherol) were characterized, and the antioxidant activity of dried WPI coatings against lipid oxidation in roasted peanuts were investigated. The AP and tocopherol were mixed into a 10% (w/w) WPI solution containing 6.7% glycerol. Process 1 (P1) blended an AP and tocopherol mixture directly into the WPI solution using a high-speed homogenizer. Process 2 (P2) used ethanol as a solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 18 publications
0
37
2
Order By: Relevance
“…The studies of natural antioxidants with edible films/coatings are increasing in the last years, a great number of works report protein based film as the principal material used but only a few use polysaccharide based films as the main material (Gómez-Estaca, Bravo, Gómez-Guillén, Alemán, & Montero, 2009;Gómez-Estaca, Montero, Fernández-Martín, Alemán, & Gómez-Guillén, 2009;Han, Hwang, Min, & Krochta, 2008;Nuthong, Benjakul, & Prodpran, 2009;Seydim & Sarikus, 2006;Sivarooban, Hettiarachchy, & Johnson, 2008). To our knowledge, no research has been done on galactomannan active films with antioxidant properties.…”
Section: Introductionmentioning
confidence: 94%
“…The studies of natural antioxidants with edible films/coatings are increasing in the last years, a great number of works report protein based film as the principal material used but only a few use polysaccharide based films as the main material (Gómez-Estaca, Bravo, Gómez-Guillén, Alemán, & Montero, 2009;Gómez-Estaca, Montero, Fernández-Martín, Alemán, & Gómez-Guillén, 2009;Han, Hwang, Min, & Krochta, 2008;Nuthong, Benjakul, & Prodpran, 2009;Seydim & Sarikus, 2006;Sivarooban, Hettiarachchy, & Johnson, 2008). To our knowledge, no research has been done on galactomannan active films with antioxidant properties.…”
Section: Introductionmentioning
confidence: 94%
“…Edible films or coatings added with natural antioxidants have been applied to fresh produce and dried foods (Das et al, 2013;Gimenez et al, 2011;Han et al, 2008;Lin et al, 2008). While an edible coating on the fresh produce itself reduces respiration and water loss, it can become more helpful by inclusion of an antioxidant to preserve the antioxidant and biochemical quality of the produce.…”
Section: Antioxidant Packagingmentioning
confidence: 99%
“…It has been described as the main oxidation product formed from linoleic acid, a polyunsaturated fatty acid present in peanuts, and it is chosen as an indicating chemical for the oxidation of peanuts (Han et al, 2008). In the present study, hexanal was the most important volatile component identified by GC-MS in the package headspace over the 10 weeks of storage.…”
Section: Monitoring Peanuts Oxidative Productsmentioning
confidence: 76%
“…To confirm these data, tests with real oxygen-sensitive products were designed. (Han, et al, 2008;Pastorelli, et al, 2006).…”
Section: Hydroxyl Radical Scavenging Activity Resultsmentioning
confidence: 99%